Visualisasi Bunga Mawar Dengan Teknik Batik Tulis Pada Selendang - Retno Yuliyandra; Eliya Pebriyeni (Institut Nalanda, 2024)
The purpose of creating this final work is to visualize the shapes of roses into the words of batik in the form of scarf cells, whose ideas came from the types of roses. The methods used in the creation of written batik buds have several stages, ranging from the preparation stage, by observing plants around, namely the author observing the rose flowers, then the elaboration stage is the observation stage carried out, the author directs the observation of roses to be used as a piece of batik, namely the stage of getting the idea, where the author's idea gets the author of the rose type of rose, then preparing the concept stage, namely preparing batik, the phase and designing for working on batik, the final method of writing is.Based on the method the author created, seven kinds of scarf with, created using a batik technique entitled: Rose Double Delight, Rose Talitha, Rose Sunsprite, Red Rose, Rose Tea Hybrid, Rose Knock Out, Black Roses.